Perancangan dan Evaluasi Sistem Absensi Karyawan Berbasis Web Berorientasi Kebutuhan Pengguna dengan Metode Prototyping - Muhammad Rivaldi; Muhammad Arif Budiman; Ardhi Maulana Yusuf; Samso Supriyatna (Journal of Science, Technology, and Innovation, 2025)
The use of information technology is increasingly needed to improve administrative processes, including attendance data. A web-based attendance system is one solution that can be used to provide fast, structured, and easily accessible attendance recording. This study aims to analyze user needs and develop a web-based online attendance system using a prototyping method. A qualitative approach was applied through observation, and questionnaires to enable researchers to understand user needs and work patterns implemented in the research environment. The prototyping process was carried out in stages using Unified Modeling Language (UML) modeling as a system design tool. This approach allows users to see the initial form of the system, identify deficiencies, and provide input that is used for continuous feature improvements. The results of the study indicate that the developed system can record attendance in real time, provide automatic recaps, and display attendance data in a more understandable format. In conclusion, this prototyping method is effective in producing an online attendance system that meets needs and improves administrative processes.